2007
DOI: 10.1291/hypres.30.1035
|View full text |Cite
|
Sign up to set email alerts
|

Association between Chronic Kidney Disease and Carotid Intima-Media Thickening in Individuals with Hypertension and Impaired Glucose Metabolism

Abstract: We investigated whether chronic kidney disease (CKD) was associated with carotid intima-media thickening

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 24 publications
2
20
0
1
Order By: Relevance
“…Our data also demonstrated that circulating omentin levels correlated inversely with creatinine levels, and positively with eGFR. Because glucose intolerance and renal dysfunction are shown to strongly associate with increased IMT, 15,16 it is reasonable that these disease conditions could affect circulating omentin levels. However, the present study suggests that omentin levels are predictive of carotid IMT, independent of glucose levels and renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also demonstrated that circulating omentin levels correlated inversely with creatinine levels, and positively with eGFR. Because glucose intolerance and renal dysfunction are shown to strongly associate with increased IMT, 15,16 it is reasonable that these disease conditions could affect circulating omentin levels. However, the present study suggests that omentin levels are predictive of carotid IMT, independent of glucose levels and renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, micro-albuminuria and renal insufficiency have been demonstrated to be associated with an increased risk for myocardial infarction or stroke 6,7) . A comparable independent relation to carotid intima media thickness was described 8) ; however, the relation of the variability of renal function…”
mentioning
confidence: 59%
“…In that study, the significant correlation between IMT and MDRD was also explained by the interaction with age 18) . In contrast, Ishizaka et al found an association between more severe CKD (individuals with either a low eGFR or albuminuria or both) and IMT 8) . In this group, MDRD was independently associated with IMT after adjustment for age, showing that this relation appears to exist in more severe cases of renal dysfunction.…”
Section: Resultsmentioning
confidence: 86%
“…Polymorphisms examined in the present study (Table I) were selected from genome-wide association studies of ischemic stroke (14) and myocardial infarction. Given that atherosclerosis is an important risk factor for CKD (15), genetic variants related to atherosclerotic disease such as ischemic stroke and myocardial infarction might also contribute to the development of CKD. We have not examined the relation of these polymorphisms in the previous studies (7,8,(16)(17)(18)(19).…”
Section: Selection Of Polymorphismsmentioning
confidence: 99%